1998
DOI: 10.1046/j.1526-100x.1998.06407.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Recover y from Lake Acidification: Zooplankton Communities as a Model of Patterns and Processes

Abstract: Knowledge of the recovery of aquatic communities from lake acidification is limited. Data from studies of crustacean zooplankton communities, however, do reveal some of the major mechanisms important in the biological recovery process. Important influences on recovery include factors related to habitat quality and the ability of organisms to colonize. During recovery, existing species and colonists from internal and external sources interact to form a new community. The relative roles of internal and external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 81 publications
1
82
0
Order By: Relevance
“…Despite the indisputable amelioration of chemical conditions, the lake still maintains its acidic status. Our study has confirmed the regional tendency of some littoral species, namely C. quadrangula and M. clavus , to fill empty niches (Keller and Yan 1998;Gray and Arnott 2009).…”
Section: Biological Recovery Of Rachelseesupporting
confidence: 80%
“…Despite the indisputable amelioration of chemical conditions, the lake still maintains its acidic status. Our study has confirmed the regional tendency of some littoral species, namely C. quadrangula and M. clavus , to fill empty niches (Keller and Yan 1998;Gray and Arnott 2009).…”
Section: Biological Recovery Of Rachelseesupporting
confidence: 80%
“…However, recovery of higher-trophic-level organisms, such as fish and benthic invertebrates, has been a much slower process, possibly because of the initial severity of damage, dispersal constraints (Stephenson and Mackie 1986, Snucins 2003, Blakely et al 2006, or the effects of persistent contaminants (Nriagu et al 1998, Arnott et al 2001, Keller and Yan 1998, Yan et al 2004. Interspecific competition and predation effects from tolerant species also have been suggested to hinder recolonization of sensitive taxa (Keller et al 1999a, Snucins 2003, Frost et al 2006, Szkokan-Emilson et al 2009).…”
mentioning
confidence: 99%
“…However, where biotic factors intervene, as revealed in recovering lakes (e.g. Keller & Yan, 1998;Holt & Yan, 2003;Vinebrooke et al, 2003;Frost et al, 2006), niches may be filled or modified by residents (Sudling et al, 2004), shifting successional endpoints as acidity declines. Although the research reported here found no evidence for competition as a mechanism limiting biological recovery, we have addressed just one competitive interaction, within the benthic food web, at one point in time.…”
Section: Leuctra Inermismentioning
confidence: 99%
“…Evidence of 'competitive resistance' has been found in acidified lake communities (e.g. Keller & Yan, 1998;Holt & Yan, 2003;Vinebrooke et al, 2003;Frost et al, 2006), where delayed recovery of algal and zooplankton communities following chemical restoration has been attributed to competition with persistent acidtolerant species, but support in streams remains circumstantial.…”
Section: Introductionmentioning
confidence: 99%